Interface shear strength variability and its use in reliability-based landfill stability analysis. Issue 1 (February 2006) - Dixon, N.; Jones, D. R. V.; Fowmes, G. J.
Abstract : Failure of modern landfills by slippage of lining materials and waste bodies is not uncommon. The majority of failures are controlled by slippage at interfaces between lining components. Information on variability of interface shear strength is required both to carry out limit equilibrium stability analysis using characteristic shear strengths and to analyse the probability of failure. Current practice is to carry out a limited number of site-specific tests, and this provides insufficient information on the variability of interface strength for design. A summary of measured strengths and an assessment of variability are presented for seven generic interfaces common in landfill lining systems. This combines values from the international literature, from an internal database, and from the results of repeatability testing programmes. The implications of variable shear strength are examined though failure probability analysis for two common design cases – veneer and waste body slippage – and this adds to the small number of studies published previously. The reliability analyses show that relatively high probabilities of failure are obtained when using variability values from the literature and an internal database, even when factors of safety ≥ 1.5. The use of repeatability data produces lower probabilities for typically used factors of safety, although they are still higher than recommended target probability of failure values.